2005
DOI: 10.1111/j.1365-2583.2004.00548.x
|View full text |Cite
|
Sign up to set email alerts
|

A novel fatty acid binding protein produced by teratocytes of the aphid parasitoid Aphidius ervi

Abstract: Aphidius ervi is an endophagous braconid, parasitoid of the pea aphid, Acyrthosiphon pisum. A. ervi teratocytes, deriving from the dissociation of the embryonic serosa, synthesize and release two major proteins into the host haemocoel. The gene of one of these proteins has been cloned and characterized. This gene codes for a 15.8 kDa protein belonging to the fatty acid binding protein (FABP) family, named Ae-FABP (A. ervi-FABP). It is abundantly present in the host haemolymph when the parasitoid larva attains … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
53
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(55 citation statements)
references
References 53 publications
(87 reference statements)
2
53
0
Order By: Relevance
“…This parasitoid is well adapted to various aphid hosts, especially the pea aphid (Acyrthosiphon pisum), the immune responses of which it usually can avoid or fight, despite strong host resistance also being known. Research has shown that the wasp venom of A. ervi, and secretions from its serosa-derived teratocytes, contain factors of A. ervi virulence, which modulate host physiology and suitability Digilio et al, Vinson et al, 2001;Falabella et al, 2000Falabella et al, , 2005. Wasp venom causes degeneration of the early embryos of the viviparous host aphid, thus redirecting host nutritional resources to the parasitoid.…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…This parasitoid is well adapted to various aphid hosts, especially the pea aphid (Acyrthosiphon pisum), the immune responses of which it usually can avoid or fight, despite strong host resistance also being known. Research has shown that the wasp venom of A. ervi, and secretions from its serosa-derived teratocytes, contain factors of A. ervi virulence, which modulate host physiology and suitability Digilio et al, Vinson et al, 2001;Falabella et al, 2000Falabella et al, , 2005. Wasp venom causes degeneration of the early embryos of the viviparous host aphid, thus redirecting host nutritional resources to the parasitoid.…”
Section: Introductionmentioning
confidence: 97%
“…These include activation of proteolytic cascades leading to localized melanization and coagulation (Cerenius and Sö derhä ll, 2004;Park et al, 2005), and hemocytic encapsulation, which is a well-known multicellular defence of insect hosts to parasitoids (Godfray, 1994;Quicke, 1997;Jiravanichpaisal et al, 2006). On the other side, to establish a permissive environment for successful parasitism, well-adapted parasitoids release factors to suppress host immunity, and to alter or even control host physiology and development (Digilio et al, 2000;Falabella et al, 2000Falabella et al, , 2003Falabella et al, , 2005Pennacchio and Strand, 2006;Zhang et al, 2006). These strategies include venom proteins (Digilio et al, 2000) and, for many parasitoids, symbiotic polyDNA viruses (Kroemer and Webb, 2004;Dupuy et al, 2006) injected by female wasps at oviposition, or factors that are secreted in the host by parasitoid embryo-derived free cells, known as teratocytes (Falabella et al, 2000(Falabella et al, , 2005.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Also, fast-growing polyploid cells called teratocytes dissociate from the serosal membrane surrounding the wasp embryo and circulate within the aphid hemocoel during larval development [29]. In A. ervi , teratocytes are known to synthesize and release two proteins that are likely involved in redirecting host resources from aphids to developing wasps: a fatty acid binding protein ( Ae -FABP), and an extracellular enolase ( Ae -ENO), which may degrade aphid tissue [30,31]. If an A. ervi female oviposited twice in a single host, she would then double the quantity of both venom and teratocytes present in the host, potentially increasing the likelihood of successful parasitism in symbiont-defended hosts.…”
Section: Introductionmentioning
confidence: 99%
“…As such, egg pronuclei are diploid and undergo meiosis, but the resulting egg pronucleus can develop into either a male larva if unfertilized or female larva if fertilized. secretory proteins from teratocytes of Aphidius ervi were identified as a fatty acid binding protein and an enolase [51,52] (Figure 2). No specific gene products have been identified from platygastroids although data do suggest that teratocyte secretory products exhibit protease activity consistent with extraoral digestion of host eggs [17].…”
Section: Current Opinion In Insect Sciencementioning
confidence: 98%